SINGKAWANG CITY GOVERNMENT STRATEGY IN RESTORING THE TOURISM SECTOR DURING THE COVID-19 PANDEMIC - Nahot Tua Parlindungan Sihaloho (DIA: Jurnal Administrasi Publik, 2021)
This study aims to describe and analyze the Singkawang City Government's strategy in recovering the private sector during the Covid-19 pandemic. The problem is that it is not yet known how Singkawang's tourism policy will deal with pandemic conditions that impact tourist destinations in this city. The research method is a descriptive type with a qualitative approach, especially related to the COVID-19 impact mitigation strategy and the implementation of Singkawang tourism policies. Then analyze the strategic elements of a policy according to Maryati and the implementation activities of the O.Jones model. Data were collected using interview, observation, and documentation techniques. The data is then analyzed using domain data analysis techniques as a researcher's effort to get a general and comprehensive (holistic) picture of the object under study. The findings concluded that 1) the tourism covid-19 impact mitigation policy strategy was connected from the national to the local level in Singkawang in the form of directives, regulations, Covid-19 mitigation programs, and stimulus for economic recovery in the tourism sector; and 2) there are no visible creative efforts based on health protocols in organizing tourism resources, methods, and unit synergies to restore tourism, the interpretation of social media-based policies on tourist visits has not been measured, and strategies have not been implemented to meet the opportunities for pandemic trend tourism types with alternative tourism models that according to health protocol.